2015
DOI: 10.1051/epjconf/20159502005
|View full text |Cite
|
Sign up to set email alerts
|

The Witten-Sakai-Sugimoto model: A brief review and some recent results

Abstract: Abstract. A brief review of the Witten-Sakai-Sugimoto model is given, which is a topdown holographic model of low-energy QCD with chiral quarks derived from type-IIA superstring theory. The main predictions of the model, in particular concerning meson spectra, the gluon condensate, the QCD string tension, the mass of the η and of baryons are discussed and compared quantitatively with available experimental and/or lattice results. Then some recent results of potential interest to the physics program at the futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 102 publications
(177 reference statements)
2
55
0
Order By: Relevance
“…Using the D4-brane construction in Witten's [30], a concrete model was proposed by Sakai and Sugimoto [31,32] which almost contains all necessary ingredients of QCD e.g. baryons [33,34], quark matter, chiral/deconfinement phase transitions [35,36,37,38], glueball spectrum and interaction [39,40,41,42,43]. Specifically, flavors are introduced into this model by a stack of N f pairs of suitable D8/D8-branes as probes embedded in the N c D4branes background.…”
Section: Introductionmentioning
confidence: 99%
“…Using the D4-brane construction in Witten's [30], a concrete model was proposed by Sakai and Sugimoto [31,32] which almost contains all necessary ingredients of QCD e.g. baryons [33,34], quark matter, chiral/deconfinement phase transitions [35,36,37,38], glueball spectrum and interaction [39,40,41,42,43]. Specifically, flavors are introduced into this model by a stack of N f pairs of suitable D8/D8-branes as probes embedded in the N c D4branes background.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this limitation, experience shows that for many quantities the unwanted modes only generate small corrections, allowing many properties of the model to be in close quantitative agreement with properties of QCD [179,196]. A useful review can be found in [200].…”
Section: Holographic Qcd: the Sakai-sugimoto Modelmentioning
confidence: 99%
“…We start with a very brief description of the model, to establish the notation and the action to which we add the quark mass correction. More detailed accounts of the Witten-Sakai-Sugimoto model can be found in the original works [1,2] and in the review [33]. The model is based on a type-IIA string theory background generated by a large number N c of D4-branes extended over the directions (x 0 , x, x 4 ), where (x 0 , x) are the 4d space-time directions.…”
Section: Brief Introduction To the Model And Dirac-born-infeld Actionmentioning
confidence: 99%